Gnathostomulida from the Otago Peninsula, southern New Zealand - Sterrer, Wolfgang (Zootaxa, 2006)
Ten species of Gnathostomulida, three new to science, are reported from the SE end of South Island, New Zealand: Haplognathia asymmetrica, H. gubbarnorum, H. rosea, H. ruberrima, Pterognathia sica, P. ugera, P. tuatara n. sp., P. portobello n. sp., Gnathostomula cf. salotae and Austrognatharia australis n. sp. This paper brings the number of species known from New Zealand to 12, of species known from the Pacific Ocean to 43, and of described gnathostomulid species worldwide to 98.